UJI VIABILITAS SERBUK SARI SECARA In-Vitro KELAPA (Cocos nucifera L.“Rangda”) DENGAN WAKTU DAN SUHU PENYIMPANAN YANG BERBEDA - Nirmala, Sista; Kriswiyanti, Eniek; Darmadi, AA. Ketut (SIMBIOSIS, 2013)
This aims of the research was to determine the structure and pollen viability of Rangda Coconut (Cocos nucifera L. “Rangda”) stored at different time and temperatures. Pollen samples were collected from Gianyar, Klungkung and Negara. The experiment was conducted at the Laboratorium of Forensic and the Laboratorium of Plant Development and Structure, Udayana University, from October 2012 to January 2013. Pollen structure was analyzed with acetolyse method, while pollen viability was analyzed in-vitro. The results showed that the structure of the pollen of “Rangda” coconut was circular, media, monosulcate, Subferoidal-Prolat, Sferoidal. Pollen viability of “Rangda" coconut was low (less than 3%). Pollen stored in the freezer has the best viability, which continually increased until the 2nd weeks, then declined after that, whie pollen viability stored at room temperature tend to decline up to the fourth weeks. Keywords: structure, viability, pollen, time, storage